Relationship Between Sports Life Satisfaction and Life Commitment - Muhammet Talha Han; Elanur Siner; Mücahit Dursun (IUC University Press, 2024)
This study investigates the relationship between Sportive Life Satisfaction and Life Commitment. The study utilized the Sportive Life Satisfaction and Life Commitment scales, with a total of 504 participants (252 male and 252 female) volunteering for the study. The factor structures of the scales were tested using IBM AMOS 24.0, and the hypotheses of the study were examined using the Statistical Package for Social Sciences version 24.0 software (IBM Corp.; Armonk, NY, USA). Given that the data set exhibited a normal distribution, parametric tests were applied. For discrete variables, an "Independent samples t-test" was conducted, while "Pearson correlation" analyses were performed for continuous variables. The results were evaluated based on the significance level of p=.050. The effect sizes of the independent variables on the dependent variables were assessed using "Cohen's d." The results of the Pearson correlation analysis indicate a positive and statistically significant relationship between Sportive Life Satisfaction and Life Commitment (r=.301, p < .01). This finding suggests that as sportive life satisfaction increases, so does life commitment. Therefore, it can be said that the satisfaction derived from sportive life contributes positively to individuals' commitment to life. This result underscores the significant impact of enjoyment from sportive life on an individual's overall experience.